The inhibitory effect of Manuka honey on human colon cancer HCT-116 and LoVo cell growth. Part 1: the suppression of cell proliferation, promotion of apoptosis and arrest of the cell cycle. Issue 4 (12th April 2018) - Afrin, Sadia; Giampieri, Francesca; Gasparrini, Massimiliano; Forbes-Hernández, Tamara Y.; Cianciosi, Danila; Reboredo-Rodriguez, Patricia; Amici, Adolfo; Quiles, Josè L.; Battino, Maurizio
Abstract : Manuka honey suppresses human colon cancer cell proliferation through the promotion of apoptosis. Abstract : Numerous investigations have been made on plant phenolic compounds and cancer prevention in recent decades. Manuka honey (MH) represents a good source of phenolic compounds such as luteolin, kaempferol, quercetin, gallic acid and syringic acid. The aim of this work was to evaluate the chemopreventive effects of MH on human colon cancer HCT-116 and LoVo cells. Both cells were exposed to different concentrations of MH (0–20 mg mL −1 for HCT-116 cells and 0–50 mg mL −1 for LoVo cells) for 48 h to measure apoptosis and cell cycle arrest as well as apoptosis and cell cycle regulatory gene and protein expression. MH exhibited profound inhibitory effects on cellular growth by reducing the proliferation ability, inducing apoptosis and arresting the cell cycle in a dose-dependent manner. Interestingly, MH treatment in non-malignant cells did not exert any significant toxicity at similar concentrations. The apoptosis event was associated with the increasing expression of p53, cleaved-PARP and caspase-3 and with the activation of both intrinsic (caspase-9) and extrinsic (caspase-8) apoptotic pathways. MH induced cell cycle arrest in the S phase in HCT-116 cells, and simultaneously, in LoVo cells, it occurred in the G2/M phase through the modulation of cell cycle regulator genes (cyclin D1, cyclin E, CDK2, CDK4, p21, p27 and Rb). The expression of p-Akt was suppressed while the expression of p-p38MAPK, p-Erk1/2 and endoplasmic stress markers (ATF6 and XBP1) was increased for apoptosis induction. Overall, these findings indicate that MH could be a promising preventive or curative food therapy for colon cancer.